2022
DOI: 10.1021/acsami.1c24257
|View full text |Cite
|
Sign up to set email alerts
|

All-Nanofiber Network Structure for Ultrasensitive Piezoresistive Pressure Sensors

Abstract: Sensing materials with fiber structures are excellent candidates for the fabrication of flexible pressure sensors due to their large specific surface area and abundant contact points. Here, an ultrathin, flexible piezoresistive pressure sensor that consists of a multilayer nanofiber network structure prepared via a simple electrospinning technique is reported. The ultrathin sensitive layer is composite nanofiber films composed of poly (3,4-ethylenedioxythiophene):poly (styrenesulfonate) and polyamide 6 (PEDOT:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…It can be concluded that the sensitivity of both the voltage and resistance responses of the Pp-250 improved after mixing the two fillers. Compared with other research results, ,,,,, the Pp-250 prepared by us has more advantages in response time and recovery time indexes and can achieve a fast and sensitive response (Figure g).…”
Section: Resultsmentioning
confidence: 64%
“…It can be concluded that the sensitivity of both the voltage and resistance responses of the Pp-250 improved after mixing the two fillers. Compared with other research results, ,,,,, the Pp-250 prepared by us has more advantages in response time and recovery time indexes and can achieve a fast and sensitive response (Figure g).…”
Section: Resultsmentioning
confidence: 64%
“…Moreover, the sol–gel process that typically involves the conversion of monomers into colloidal particle dispersion through hydrolysis and polymerization of precursors is used to prepare Na 0.5 K 0.5 NbO 3 nanosheet and ZnO nanosheet . In addition to thin film and colloidal nanoparticle, inverse opal scaffolds and electrospun nanofibers are also used as a piezoelectric nanoplatform for biomedical application …”
Section: Construction Of Piezoelectric Nanoplatforms For Wireless The...mentioning
confidence: 99%
“…(a) Schematic representation of piezoelectric nanomaterial-based pressure sensor for health-monitoring applications. Adapted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Piezoelectric Nanomaterials For Wireless Therapy Via Ultraso...mentioning
confidence: 99%
See 2 more Smart Citations